RANCANGAN PENEMPATAN ACCESS POINT UNTUK MENDUKUNG LAYANAN E-LEARNING DI AREA KAMPUS TEKNIK ELEKTRO UNIVERSITAS UDAYANA - FEBY PRADIPTA, PUTU; SUKADARMIKA, GEDE; DIAFARI DJUNI H, I Gst A. KOMANG (Jurnal SPEKTRUM, 2019)
The development of information technology in the field of education has developed very rapidly, e-learning is one example of the development of information technology of education. To optimize the e-learning system in an area, adequate network infrastructure is needed. This research aims to improve the WLAN (Wireless Local Area Network) network infrastructure in the campus area of the Electrical Engineering Study Program, Faculty of Engineering, Udayana University, Bukit Jimbaran. This research was conducted in 3 stages, namely measuring the capacity and range of access points directly, calculating the access point signal level, and using simulations to calculate the number and range of access points using the Atoll Rf Planning software. Based on the results of measurements and calculations obtained, the results of the 3 stages of the research carried out found the farthest range of indoor and outdoor access points each 12 meters and 22.6 meters. The total number of access points needed for indoor and outdoor positions as a whole in accordance with the simulation results requires as many as 22 access points.